2003
DOI: 10.1093/aje/kwg056
|View full text |Cite
|
Sign up to set email alerts
|

Does Male Age Affect the Risk of Spontaneous Abortion? An Approach Using Semiparametric Regression

Abstract: Couples in industrialized countries tend to delay attempting to have children, which may lower their chances of livebirth. The authors assessed the association between male age and the risk of spontaneous abortion between weeks 5 and 20 of pregnancy, controlling for female age. They interviewed by telephone a random cross-sectional population of 1,151 French women who had been pregnant between 1985 and 2000 (participation rate, 73%). A total of 12.2% of the 2,414 pregnancies resulted in spontaneous abortion. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 55 publications
2
35
0
4
Order By: Relevance
“…Similarly, Ford and peers analyzed risk factors for miscarriage in couples who achieved a recognized pregnancy, observing that the risk of miscarriage was higher in couples with males above 35 years old [58]. Similar results were found by several other authors that concluded that adverse pregnancy outcomes are related to APA, and reach a peak if both partners are of advanced age [59][60][61]. A casecontrol study by Kleinhaus and peers similarly verified a correlation between APA and miscarriage risk, independent of maternal age [64].…”
Section: Spontaneous Abortion Ratessupporting
confidence: 69%
“…Similarly, Ford and peers analyzed risk factors for miscarriage in couples who achieved a recognized pregnancy, observing that the risk of miscarriage was higher in couples with males above 35 years old [58]. Similar results were found by several other authors that concluded that adverse pregnancy outcomes are related to APA, and reach a peak if both partners are of advanced age [59][60][61]. A casecontrol study by Kleinhaus and peers similarly verified a correlation between APA and miscarriage risk, independent of maternal age [64].…”
Section: Spontaneous Abortion Ratessupporting
confidence: 69%
“…Another retrospective analysis of 2414 pregnancies with a 12.2% rate of spontaneous miscarriage confirmed deleterious paternal age effects with a significant increase in risk for spontaneous miscarriage when men were older than 35 years (Slama et al, 2003). Unexpectedly this difference was only seen among couples in which the woman's age was ,30 years, which could be explained by the fact that maternal risk factors for spontaneous miscarriage might be better controlled by the adjustment for maternal age in younger than older women, in whom other factors, not adjustable by the maternal age, may mask the paternal age effect (Slama et al, 2005).…”
Section: Paternal Effectsmentioning
confidence: 90%
“…Some studies have shown increased age-related numerical and structural sperm chromosomal abnormalities, changes in sperm DNA methylation, and a higher mutational load (6)(7)(8). Epidemiologic data suggest that increasing male age may be associated with pregnancy loss (9) and with a range of birth defects (10).…”
mentioning
confidence: 99%